Financial pecking order and the value platform of intellectual capital: Observing the Finnish biotechnology industry - Antti-Jussi Tahvanainen; Raine Hermans (The Research Institute of the Finnish Economy (ETLA), 2004)
This study analyzes the question how the intellectual capital (IC) of a company affects its financial capital structure. To this end we consecutively apply the methods of factor and regression analyses on a sample of 65 small and medium sized Finnish biotechnology companies. Based on the results we find that firms with a well-balanced IC base finance their operations to a larger extent with retained earnings and debt while companies with less wellbalanced IC bases revert to other sources of financing, for example, capital loans and external equity. Utilizing Myers' (1984) pecking order theory as a theoretical backdrop we are able to show potential rationales behind deviating capital structure choices made by companies with dissimilar IC bases.
Keywords: 330; Biotechnische Industrie; Klein- und Mittelunternehmen; Kapitalstruktur; Humankapital; Finnland